Tinjauan Regulasi Persekutuan Firma Dan Persekutuan Komanditer Pada Tatanan Hukum Indonesia - Muslih Muslih; Andre Febrian Perdana (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Article 23 of the Commercial Code stipulates that registration shall be filed through the Registrar's Office of the District Court of the jurisdiction where the company is domiciled. Whereas in Article 3 Paragraph (2) Permenkumham No. 17 of 2018 says that registration is submitted through the Business Entity Administration System (SABU). Seeing this, the issue of the existence and binding force of the laws and regulations regulated in Article 8 paragraph (1) of Law no. 12/2011, including the Ministerial Regulation, does not only regulate the existence of laws and regulations on a delegation basis. issuance of a new regulation regarding the establishment and registration of limited partnerships/CV in the business entity administration system (SABU) in accordance with the provisions of Article 5 paragraph (1) of the Regulation of the Minister of Law and Human Rights Number 17 of 2018 concerning Registration of limited partnerships, firm partnerships and civil partnerships which previously was only regulated in the Criminal Code. This research uses normative juridical research methods. The first conclusion is drawn, with the enactment of Permenkumham No. 17 of 2018, CV registration is easier and more organized and this also makes it easier for investors to get information about CVs that have been registered on SABU. Problems with establishing a CV from Permenkumham No. 17 of 2018 is the first, the establishment of a CV must order a name first before finally registering the CV on SABU. Second, the place for CV registration is changed to SABU. Third, the establishment of a CV is required to use an authentic deed.